2021
DOI: 10.3390/molecules26072080
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Silico Screening and Characterization of Antimicrobial Napin Bioactive Protein in Brassica juncea and Moringa oleifera

Abstract: The study aimed to investigate the antibacterial activity of Mustard (Brassica juncea) and Moringa (Moringa oleifera) leaf extracts and coagulant protein for their potential application in water treatment. Bacterial cell aggregation and growth kinetics studies were employed for thirteen bacterial strains with different concentrations of leaf extracts and coagulant protein. Moringa oleifera leaf extract (MOS) and coagulant protein showed cell aggregation against ten bacterial strains, whereas leaf extract alone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…oleifera flour. In a previous study, the coagulant proteins, the compound aglycone of deoxy-Niazimicine, and the phenolic compounds from M. oleifera leaves and flour showed antibacterial activities against thirteen pathogenic microorganisms . Dasgupta et al (a) found that the cationic protein from M.…”
Section: Introductionmentioning
confidence: 98%
“…oleifera flour. In a previous study, the coagulant proteins, the compound aglycone of deoxy-Niazimicine, and the phenolic compounds from M. oleifera leaves and flour showed antibacterial activities against thirteen pathogenic microorganisms . Dasgupta et al (a) found that the cationic protein from M.…”
Section: Introductionmentioning
confidence: 98%
“…Synthetic peptides have been proposed to be the ideal inhibitors of enzyme activity either alone or in combination with small-molecule drugs [40]. Chandrashekar S. et al conducted a study, where the protein NAP1 inhibited a S. aureus gyrase-AM8191 complex [41]. Molecular modelling study revealed that peptide P1 and P3 interacted with Topoisomerase IV of E. faecalis and formed hydrogen bonds with Ans650 as a reference antibiotic used in the treatment-levofloxacin.…”
Section: Discussionmentioning
confidence: 99%
“…Peptides of hypotensive efect were isolated from MO as angiotensin-converting enzyme (ACE), Gly-Leu-Phe-Phe (GLFF), and renin peptides Leu-Gly-Phe-Phe (LGF) [51]. Many peptides of antimicrobial agents have been purifed from MO proteins [215]. Another peptide (<7.5 kDa) has been isolated from MO and possessed an efcient antimicrobial activity [216].…”
Section: Moringa Oleifera and Proteinsmentioning
confidence: 99%